Design and synthesis of iminosugar-based inhibitors of glucosylceramide synthase: the search for new therapeutic agents against Gaucher disease - Boucheron, C; Desvergnes, V; Compain, P; Martin, O; Lavi, A; Mackeen, M; Wormald, M; Dwek, R; Butters, T (2005)
A series of iminosugars bearing two or three alkyl chains ('iminoglycolipids') were designed as ceramide mimics and analogues of N-butyl 1-deoxynojirimycin (N-Bu DNJ, Zavesca®). This orally active iminosugar inhibits the biosynthesis of glucosylceramides, which accumulate pathologically in macrophages of patients with Gaucher disease (substrate reduction therapy, SRT). Molecular modeling and kinetic experiments have suggested that N-Bu DNJ is a competitive inhibitor that mimics the ceramide acceptor but not the donor substrate (UDP-glucose) in the glucosylceramide synthase-catalyzed process. Kinetic measurements were made with the glucosyltransferase to assess the selectivity of the new iminoglycolipids with respect to the length (C4 or C8) and the position of the second alkyl chain (C-1, O-2 and/or O-4). This structure-activity relationship study showed that the addition of a second alkyl chain, to obtain better ceramide mimics, led to less potent inhibitors. Moreover, the synthase active site did not discriminate inhibitors differing by the position of the second alkyl chain (C-1, O-2 or O-4). Best inhibition was found for 1,5-dideoxy-1,5-imino-N-octyl-4-O-octyl-d-glucitol (IC50 134 μM). © 2005 Elsevier Ltd. All rights reserved.